Alih Aksara dan Alih Bahasa Teks Tafsir Ayat Ya Ayyuhannas - Rosi Dayanti; Nurizati Nurizati; Muhammad Adek (Diwan: Jurnal Bahasa dan Sastra Arab, 2020)
The purpose of this research is to: (a) describe the physical formof Tafsir Ayat Ya Ayyuhannas manuscript by Haji Abdul LatifSyakur; (b) display the transliteration result of Tafsir Ayat YaAyyuhannas text by Haji Abdul Latif Syakur; and (c) present thetranslation result of Tafsir Ayat Ya Ayyuhannas text by Haji AbdulLatif Syakur. This research was classified as philology research.The result of this research is: (1) the description of Tafsir Ayat YaAyyuhannas manuscript by Haji Abdul Latif Syakur; (2) thetransliteration of Tafsir Ayat Ya Ayyuhannas text by Haji AbdulLatif Syakur from Arabic-Malay script to Latin script; (3) thetranslation of Tafsir Ayat Ya Ayyuhannas text by Haji Abdul LatifSyakur was translated from old Malay to Indonesian.